Volatility in the Stock Market- An Examination of the Indian Context - Mr. Ashok Prem; Mr. Maulik Chandnani; Mr. Sunny Masand (Journal of Advanced Zoology, 2022)
The stock market is a pivotal component of the financial system, playing a vital role in economic development. It serves as a platform where investors can trade various securities, such as shares, bonds, and debentures, without any restrictions. Listed company stock market to raise capital through public offerings, attracting long-term investors seeking profits. In India, major stock exchanges include es utilize the Bombay Stock Exchange (BSE), the National Stock Exchange (NSE), and the Calcutta Stock Exchange (CSE), which collectively represent the largest Indian stock markets. Volatility, a measure of the dispersion of returns for a given security or market index, carries implications for risk assessment. Higher volatility typically indicates greater risk associated with the security. Accurate estimation of volatility is crucial for market participants, as it informs investment decisions and risk management strategies. While developed markets historically offer higher returns with volatility over extended periods, India’s market is progressively becoming more informationally efficient compared to develop lower ed counterparts. This study aims to provide insights into the historical, current, and future dynamics of the Indian stock market.